The Septuagint and its reception: collected essays - Meiser, Martin (Wissenschaftliche Untersuchungen zum Neuen Testament, 2022)
Cover -- Title -- Preface -- Table of Contents -- The Septuagint and Its Interpretation -- Annotations on Theology in Ancient Scholarship on Homer and the Concept of God in the Septuagint -- Historiographic Tendencies in the Septuagint -- The Septuagint Translation of the Books of Kings in the Context of the History of Early Jewish Literature -- The Septuagint of Samuel and the Targum Jonathan -- The Temple Construction Report 1Kgs 6 - How Translators Deal with a Difficult Template -- Interpretive Methods in the Septuagint of the Prophetic Books -- Phenomena of Prophecy in the Septuagint -- Conceptions of God's Dwelling in the Septuagint -- Septuagint and New Testament -- Septuagint Quotations in the Gospel of Mark -- Septuagint Quotations in Acts -- The Torah in Galatians -- The Torah in the Ethics of Paul -- Textual Criticism of Patristic Quotations of the Septuagint -- Bible Quotations in Greek and Latin Patristic Texts -- New Testament Quotations of the Septuagint within Patristic Literature - A Study on Textual Criticism and Hermeneutics -- New Testament Quotations of the Septuagint in the Works of Justin Martyr -- Jerome as Textual Critic -- Antiochene Readings of I-IV Reigns in Early Church Fathers -- Interpretation of Old Testament Texts in Ancient Christian Literature -- The Impact of Reception History for the Research on the Septuagint -- Jealousy, Unrighteousness and Ignorance of God? Ancient Jewish and Christian Exegetes on Questionable Texts in the Book of Genesis -- Adam in Patristic Literature - Some Issues of Anthropology and Ethics -- Abraham and His Family in Ancient Greek and Latin Exegesis -- Gen 28:10-22 in Ancient Jewish and Christian Reception -- The "Song of Hannah" (1Sam 2:1-10) and Its Reception in Ancient Judaism and Christianity -- Ancient Christian Exegesis of Psalms and Ancient Philology on Homer.